Steady-State Serum IgG Trough Levels Are Adequate for Pharmacokinetic Assessment in Patients with Immunodeficiencies Receiving Subcutaneous Immune Globulin - Li, Zhaoyang (J Clin Immunol, 2021)
Patients with primary immunodeficiency diseases often require lifelong immunoglobulin (IG) therapy. Most clinical trials investigating IG therapies characterize serum immunoglobulin G (IgG) pharmacokinetic (PK) profiles by serially assessing serum IgG levels. This retrospective analysis evaluated whether steady-state serum IgG trough level measurement alone is adequate for PK assessment. Based on individual patient serum IgG trough levels from two pivotal trials (phase 2/3 European [NCT01412385] and North American [NCT01218438]) of weekly 20% subcutaneous IG (SCIG; Cuvitru, Ig20Gly), trough level-predicted IgG AUC (AUC(τ,tp)) were calculated and compared with the reported AUC calculated from serum IgG concentration-time profiles (AUC(τ)). In both studies, mean AUC(τ,tp) values for Ig20Gly were essentially equivalent to AUC(τ) with point estimates of geometric mean ratio (GMR) of AUC(τ,tp)/AUC(τ) near 1.0 and 90% CIs within 0.80–1.25. In contrast, for IVIG, 10%, mean AUC(τ,tp) values were lower than AUC(τ) by >20%, (GMR [90% CI]: 0.74 [0.70–0.78] and 0.77 [0.73–0.81] for the two studies, respectively). Mean AUC(τ,tp) values calculated for 4 other SCIG products (based on mean IgG trough levels reported in the literature/labels) were also essentially equivalent to the reported AUC(τ) (differences <10% for all except HyQvia, a facilitated SCIG product), while differences for IVIG products were >20%. In conclusion, steady-state serum IgG levels following weekly SCIG remain stable, allowing for reliable prediction of AUC over the dosing interval using trough IgG levels. These findings indicate that measuring steady-state serum IgG trough levels alone may be adequate for PK assessment of weekly SCIG. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10875-021-00990-z.